The Holocaust between Pop Literature and High Literature: Maxim Biller’s Inside the Head of Bruno Schulz - Ibler, Reinhard (Poznańskie Studia Slawistyczne, 2023)
Maxim Biller, one of the most prominent, but also most controversial German-Jewish authors, is an important figure in modern Holocaust literature. After a short introduction to his early journalistic and literary oeuvre dealing with the Holocaust, we will focus on his novella Inside the Head of Bruno Schulz from 2013. A short outline of the story will be followed by a detailed analysis of the role the Holocaust plays in this story, especially with regard to the two protagonists, Bruno Schulz and Thomas Mann. It will be shown that the pop-literary provocations that dominate Billers’ early works, are now displaced by clear tendencies towards a high literary, artistic standard, which are characteristic for the developments of modern Holocaust literature in general.